Effect of fatty acid anilides on immune responses of Swiss mice. - Blasco, R (1992)
The possible relationship between fatty acid anilides and the toxic oil syndrome (TOS) which appeared in Spain in 1981 has been debated during recent years. These anilides have been detected as anomalous compound in toxic oils analysed. After treatment with one daily dose of 50 mg/kg of oleilanilide (88.86% pure) for 5 days, animals showed a tendency towards progressive loss of body weight and a significant increase in serum concentration of immunoglobulins. The percentage of suppressor T cells in spleen diminished significantly compared with the control group. Consequently, an increase in the helper T cells/suppressor T cells was also observed. The production of IgM and IgG in culture was significantly higher than in controls and no differences were seen in IgA synthesis. The functional studies of generation of specific IgM, IgA and IgG suppressor cells at variable doses of concanavalin A (Con A) showed paradoxical behaviour of suppressor T cells generated by low doses of Con A. A similar change occurred at higher doses of Con A. These results suggest that low-dose treatment with oleilanilides induces an alteration in the immune response in Swiss mice.